Why Smoke Flavor Capsule Cigarettes? Preferences and Perceptions Among Adult Smokers in Mexico. Issue 10 (4th March 2022) - Ogunnaike, Adebusola; Gallegos-Carrillo, Katia; Barrientos-Gutierrez, Inti; Arillo Santillán, Edna; Cho, Yoo Jin; Thrasher, James F
Abstract: Introduction: Flavor capsule cigarettes are rapidly gaining global market share, particularly in Latin America; however, little is known about consumer profiles and perceptions since the diffusion of this product innovation has become more widespread. Aims and Methods: This paper compares profiles and perceptions of smokers who prefer flavor capsule cigarettes and those who do not in Mexico. We analyzed data from six online surveys of adult Mexican smokers ( n  = 4488) from 2018–2020. Participants identified their preferred brand variety characteristics (no capsule; one capsule; two capsules), and reported perceptions of their brand varieties' flavor, smoothness, harmfulness, and whether they smoke to control their appetite. Separate multinomial logistic models regressed preferred cigarette type on sociodemographic and smoking-related variables, as well as perceived benefits on preferred cigarette type, adjusting for covariates. Results: Most participants preferred capsule cigarettes (single capsule = 47.5%; double capsule = 12.9%). Flavor capsule users reported that their preferred varieties mostly tasted like menthol/mint (59% of single capsule users and 23% of double capsule users), cucumber (12% and 27%, respectively) or berries (10% and 22%, respectively). Females were more likely than males to prefer either single or double capsule cigarettes (AOR = 2.26 and 2.01, respectively). Preference for flavor capsules was also higher among younger smokers, e-cigarette users, those who smoke less frequently, and those who recently tried or plan to quit. Smokers who preferred capsules were more likely than non-capsule smokers to perceive their cigarettes as smoother, less harmful, and to smoke to control their appetite. Conclusions: The high prevalence of capsule use and widespread perceptions of the benefits of capsules over traditional cigarettes may help explain why tobacco control policies have not reduced smoking prevalence in Mexico. Implications: Flavor capsules are rapidly growing in popularity in many countries around the world, including Mexico. This study found that more Mexican adult smokers prefer brand varieties with capsules (60%) than without capsules (40%), that flavor capsule use strongly correlates with menthol cigarette use, and that perceived flavors of capsules range widely. Flavor capsule smokers have more positive smoking expectancies (eg, lower risk perceptions, dietary control) than noncapsule smokers. Capsules appeal particularly to women, young adults, less frequent smokers, and those who recently tried to quit. Policies should consider banning flavors in cigarettes, including capsules and other filter innovations.